1984
DOI: 10.1136/jech.38.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Validity of maternal reporting of breast feeding history and the association with blood lipids in 17 year olds in Jerusalem.

Abstract: SUMMARYThe validity of mothers' reporting of the breast feeding history of their children more than 20 years after their birth was studied in a Jerusalem population. Among 74 study subjects, duration of breast feeding as ascertained from an interview was well correlated with that recorded in mother and child health clinic charts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 17 publications
6
79
1
3
Order By: Relevance
“…Although the studied population had a high level of schooling, and although a number of studies show evidence of reasonable accuracy for information provided by mothers regarding the length for which their children were breastfed, 6,8,10 it is possible that this information was not sufficiently precise in the present study. Such lack of precision would tend to obscure eventual associations between duration of breastfeeding and school-age obesity, driving the odds ratios towards the unit.…”
Section: Discussionmentioning
confidence: 88%
“…Although the studied population had a high level of schooling, and although a number of studies show evidence of reasonable accuracy for information provided by mothers regarding the length for which their children were breastfed, 6,8,10 it is possible that this information was not sufficiently precise in the present study. Such lack of precision would tend to obscure eventual associations between duration of breastfeeding and school-age obesity, driving the odds ratios towards the unit.…”
Section: Discussionmentioning
confidence: 88%
“…However, the parents were asked to confirm the data on breast feeding from well-baby clinic medical records, a fact that increases reliability of infant nutritional data. It has also been shown that maternal recollection of their children's infant feeding remains accurate up to 20 years after birth (Kark et al, 1984). Unfortunately, we did not have data to separate those subjects who were exclusively breast fed (with no addition of any formula or other milks) or partially breast fed.…”
Section: Discussionmentioning
confidence: 98%
“…42 In this context, our prospective birth cohort study may have several advantages: (1) The data were collected close to their origination, ensuring a high degree of validity and precision of any early influences as well as later outcomes. Recall bias did not constitute a problem.…”
Section: Study Design Aspectsmentioning
confidence: 99%